(untitled) (American Journal of Arts and Human Science, 2024)
The Kalesa, a traditional horse-drawn carriage, has been an iconic symbol of Filipino culture and heritage for centuries. However, in recent years, the once vibrant Kalesa industry in Laoag City, Ilocos Norte, has been facing a steady decline. This research abstract aims to investigte the factors contributing to the demise of this traditional mode of transportation and its associated industry. Through a combination of qualitative interviews, this study examines the socio-economic, cultural, and environmental factors that have led to the dwindling presence of Kalesas in Laoag City. Furthermore, historical research was done to look at primary sources and secondary documents on the Kalesa’s contribution to the city’s growth, especially in terms of its local economy and distinctive features that let people appreciate its local color even more.